EFFECT OF PRE- AND POST-MATING VITAMINS AD3E TREATMENT ON REPRODUCTIVE PERFORMANCE OF AWASSI EWES - T. A. Abdulkareem,; S. M. Eidan,; F. K. Al-Saidy,; N. K. Al-Hassani, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was designed to investigate the influence of pre-estrus (PE) synchronization and post-mating (PM) vitamins AD3E treatment on the reproductive performance of Awassi ewes raised at four Iraqi provinces. Seventy six Awassi ewes were randomly divided within each province into two groups. The first group (n=15, except for Karbala, n= 11) were im injected with five AD3E injections (150 IU / dose), biweekly interval. The 1st injection was 1.5 months PM, while the 2nd and 3rd injections were at the time of progestagen-impregnated vaginal sponges insertion. The 4th injection was at the time of the vaginal sponge’s removal, whereas the 5th injection was 14 days PM. The control group (n=5) was intramuscularly injected with 5 ml normal saline at similar periods. The AD3E groups exhibited higher (P≤0.01) fertility and conception rates as compared to the control groups in Al-Najaf and Karbala provinces. Higher (P≤0.01) lambing rate and liter size were noticed in AD3E groups than those of the control group for all provinces. In conclusion, pre-estrus synchronization and post-mating vitamin AD3E treatment improved the reproductive performance of Awassi ewes.